Peran Dosen dalam Mengembangkan Inovasi Pembelajaran Berbasis Teknologi Digital: Studi Kasus di Sekolah Tinggi Ilmu Ekonomi Balikpapan - Maisurah, Anisah; Falah, Nur Azizah; Raihani, Raihani; Aisyah, Siti; Anhar, Anhar (Lembaga Intelektual Muda (LIM) Maluku, 2025)
In the era of digital transformation, lecturers have a strategic role as facilitators and innovators in the learning process to create an academic environment that is adaptive to technological developments. This study aims to analyze the role of lecturers in developing technology-based learning innovations at the Sekolah Tinggi Ilmu Ekonomi (STIEPAN). This study uses a qualitative approach with a case study method. Data collection techniques are carried out through three main methods, namely semi-structured in-depth interviews, non-participatory observation, and documentation. Data analysis uses the Miles and Huberman model, which consists of data reduction, data display, and drawing conclusions, supported by NVivo 12 software for coding and categorizing findings. The research results show that lecturers at STIEPAN have utilized various digital technologies, such as the Academic Information System (SIAKAD), online conferencing applications, and academic social media, to enhance interaction, effectiveness, and flexibility in learning. However, some obstacles were also found, such as limited technological competence and supporting facilities. Overall, this study emphasizes the importance of improving lecturers' digital literacy as well as institutional support in promoting sustainable learning innovation at higher education institutions